Ocena rabe lesa v energetske namene na primeru občine Šentjur - Polnar, Zoran (Gozdarski vestnik, 2016)
In the light of the objectives of the EU directives and Slovenian action plans for an increased use of wood for energy, this article examines the availability and utilization of wood for energy in the municipality. A brief introduction on the advantages and disadvantages for the society as a whole, arising from the increased use of wood for energy purposes, is followed by the presentation of methodology for assessing the availability of wood in the municipality for its use in large boilers for heating public facilities and to meet the needs of industry in the municipality as well as for domestic heating. In this context we considered four possible scenarios relating to felling and devoted special attention to assortimentation. We have relied upon domestic and foreign research and applied SWOT analysis which is used to generate factors affecting the utilization of wood for energy in the municipality. Through surveys, the experts compared the individual SWOT factors. The survey results were analyzed using AHP method, which ranks the factors according to their importance. Presented methodology was applied in the case of Šentjur Municipality. The source of data for the research consists of data from the national forest inventory and the local energy concept for the municipality Šentjur. Within the limits of the Šentjur Municipality, there are sufficient quantities of wood for a possible district heating project, but the availability of biomass is not satisfying for now, since it depends heavily on the majority share of privately owned forests and fragmented structure, present in the vast majority of the municipality. To raise the availability of biomass, innovative measures are necessary, as well as efforts of owners to join, especially small shareholders. The factor, impacting the possibility of using wood for energy purposes in large boilers of Šentjur Municipality most positively, is the presence of infrastructure for storage and processing, while non-use of modern technologies for harvesting and skidding, and a small percentage of conifers in the timber stock represent an important negative impact.
Keywords: les; energetska raba lesa; use of wood for energy; razpoložljivost lesa; wood availability; SWOT; large boilers; Šentjur; AHP; velike kurilne naprave; Šentjur Municipality